A high-speed neural analog circuit for computing the bit-level transform image coding - Chang, P.R.; Hwang, K.S.; Gong, H.M. (IEEE transactions on consumer electronics, 1991)
A Hopfield-type neural network approach is presented which leads to an analog circuit for implementing the bit-level transform image. The computation of a 2D DCT (discrete cosine transform)-based transform coding is shown to solve a quadratic nonlinear programming problem subject to the corresponding 2's complement binary variables of 2D DCT coefficients. A novel Hopfield-type neural analog circuit designed to perform the DCT-based quadratic nonlinear programming could obtain the desired coefficients of an 8*8 DCT in 2's complement code within 1 ns with RC=10/sup -8/. A programmable analog MOS implementation provides a flexible architecture to realize the DCT-based neural net.< >